Measuring the flow and the turbulence in a harsh environment using a modified Mc Caffrey gauge. (August 2021) - Proust, Christophe; Jamois, Didier
Abstract: Considering that many laboratory measurement techniques devoted to fluid mechanics are difficult to implement in field, especially for combustion and explosions, the present authors developed during the last 2 decades, a special type of Mc Caffrey gauges to measure the flow and the turbulence in those harsh situations (Fig. 1). Especially a fully embedded version is now under development and the initial work about this innovation is evoked. In this paper, the theory underpinning this technique is presented together with some technical details. Limitations are given and comparisons with reference techniques (hot wire in air jets) are presented. Highlights: The theory attached to turbulence measurement with bidirectional probe is explained. Signal process is used to discuss performances and limitation by comparison with reference hot wire measurements. Metrological limits highlighted are mainly attributed to probe geometry: volume of the head and pipes length of the sensor. Some acoustic resonance may superpose on the turbulence signals affecting the turbulence spectrum. The head of the probe is expected to interact significantly on the turbulent eddies only when the integral scale of the turbulence is similar to the diameter of the head. Geometrical features are not a limitation for field experiments for which this kind of probe is principally designed for. The bidirectional probe concept offers significant robustness and might be one of the only mean to measure turbulence, especially if the flow is unclean (dust, soot, moisture, ..). Improvements are possible but would require a profound redesign of the head of the probe and of the pressure sensor.